Climbing fiber signaling and cerebellar gain control - Ohtsuki, Gen; Piochon, Claire; Hansel, Christian (Frontiers in Cellular Neuroscience, 2009)
The physiology of climbing fiber signals in cerebellar Purkinje cells has been studied since the early days of electrophysiology. Both the climbing fiber-evoked complex spike and the role of climbing fiber activity in the induction of long-term depression (LTD) at parallel fiber-Purkinje cell synapses have become hallmark features of cerebellar physiology. However, the key role of climbing fiber signaling in cerebellar motor learning has been challenged by recent reports of forms of synaptic and non-synaptic plasticity in the cerebellar cortex that do not involve climbing fiber activity, but might well play a role in cerebellar learning. Moreover, cerebellar LTD does not seem to strictly require climbing fiber activity. These observations make it necessary to re-evaluate the role of climbing fiber signaling in cerebellar function. Here, we argue that climbing fiber signaling is about adjusting relative probabilities for the induction of LTD and long-term potentiation (LTP) at parallel fiber synapses. Complex spike-associated, dendritic calcium transients control postsynaptic LTD and LTP induction. High calcium transients, provided by complex spike activity, do not only favor postsynaptic LTD induction, but simultaneously trigger retrograde cannabinoid signaling, which blocks the induction of presynaptic LTP. Plasticity of the climbing fiber input itself provides additional means to fine-tune complex spike associated calcium signaling and thus to adjust the gain of heterosynaptic climbing fiber control. In addition to dendritic calcium transients, climbing fiber activity leads to the release of the neuropeptide corticotropin-releasing factor (CRF), which facilitates LTD induction at both parallel fiber and climbing fiber synapses.